ANALISIS KONSEPSI SISWA PADA MATERI KEANEKARAGAMAN HAYATI DI SMA - Septian, Irwin; Ariyati, Eka; Marlina, Reni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This study aimed to analyze the students' conceptions and calculating thepercentage of students’conceptions on material biodiversity in class X SMAN 1Pontianak which include: the diversity of genes, species and ecosystems,biodiversity of Indonesia (genes, species, ecosystems) flora, fauna andmicroorganisms, Wallace’s and Weber’s line also the uniqueness of the tropicalrain forests in Indonesia. The method used is descriptive method with a surveyform. Subjects in this study were students of class X Math and Science 1 and 2SMAN 1 Pontianak. The instrument used is a diagnostic test multiple choice,along with the reasons. Based on the recapitulation of the student profile in thematerial conception of biodiversity gained an average of conformityconceptions of students in the scientific concept 52.21%, misconceptions47.50%, and 0.29% of students did not answer or omit.Keywords: Analysis, students' conceptions, Biodiversity